PL1.2 Multiparametric assessment of factors influencing 2 HG accumulation in diffuse brain gliomas. (6th September 2019) - Nichelli, L; Branzoli, F; Valabregue, R; Capelle, L; Ottolenghi, C; Bielle, F; Lerond, J; Giry, M; Villa, C; Galanaud, D; Lehéricy, S; Marjańska, M; et al.
Abstract: BACKGROUND: 2-hydroxyglutarate (2HG) can be detected non-invasively in IDH-mutant gliomas by in vivo magnetic resonance spectroscopy (MRS). We investigated factors affecting 2 HG accumulation and explored the prognostic value of 2 HG detection in IDH mutant gliomas and 2 HG variations during anti-cancer therapies. MATERIAL AND METHODS: We prospectively scanned by MEGA-PRESS 70 glioma patients (24 before surgery and 46 IDH mutant operated glioma) and measured 2HG. CRLB cut-off was 50%. We followed up 9 IDH mutant patients during radiotherapy and chemotherapy.We analyzed radiological parameters (tumor and cystic/necrotic volumes, fractions of VOI filled with tumor, spectroscopic profile, "infiltrative" versus "expansive" morphology, contrast-enhancement) and genetic profile (IDH1, IDH2, 1p19q codeletion). 2HG concentrations in plasma, urine, and surgical obtained samples were measured by gas chromatography-mass spectrometry (GC-MS). RESULTS: MEGA-PRESS sequence detected 2HG with a sensitivity of 95% in untreated patients, and of 69% in pre-treated patient. Positive predictive value was 100% in both groups. 2HG was lower in pre-treated IDH mutant gliomas (1.1 versus 2.3 mM, P=0.02) and decreased rapidly during radiotherapy and chemotherapy before any radiological change. 2HG detection was positively correlated with tumor volume (P=0.02), choline measurements (r=0.58 P<0.0001), cellular density (measured by restricted diffusivity, Pearson r -0.40 P=0.01), "expansive" presentation, mutated reads/total reads ratio by NGS and was inversely correlated with Myo-inositol (Pearson R -0.29 P=0.03) and cystic/necrotic areas (P=0.04). 2HG by MRS positively correlated with urine 2HG (r=0.80 P=0.003). 2 HG was higher in IDH2 mutant (4.7 versus 2.4 Mm, P=0.02) and lower in non R132H IDH1 mutant (1.12 mM P=0.004). Among IDH mutant glioma patients, 2 HG detection was associated with longer survival (HR 0.09; 95%CI 0.018–0.52). CONCLUSION: Tumor volume, cellular density, previous radio- and chemotherapy and genetic features determine 2 HG detection in IDH mutant gliomas. 2 HG detection is associated with better outcome and can be reliably monitored during anti-cancer treatments.